Off-Canon pleasures a case study and a perspective - Frank, Armin Paul (Universitätsverlag Göttingen, 2011)
The inclusion of works in a canonical list creates a large body of exclusions. But among these neglected works there are not a few that nevertheless are worth reading. Literary worth is not necessarily aesthetic impeccability. A literary work recommends itself by a high degree of artistic achievement with elbowroom for historical importance. The present study focuses on Leo Rosten's immigration novel The Education of Hyman Kaplan (1937) and Archibald MacLeish's radio play Air Raid (1938). The first is more than the apparent compendium of language-based jokes. Read in the context of immigration policy from Presidents Theodore Roosevelt to F. D. Roosevelt and of Jewish-American humor, it displays Kaplan's moral and intellectual growth, which extant commentary denies, and exhibits the "interior internationality" of an immigration country. Air Raid is one of the few achieved American radio plays to take a stand on foreign affairs in a context that does not only consist of broadcasting and Picasso's collage-painting Guernica - the "screaming picture" which MacLeish transposed into the acoustic medium - but also of the historical saturation bombing of the Basque town.